Carbapenem Resistance Related with Biofilm Formation and Pilin Genes in Clinical Pseudomonas aeruginosa Isolates - Tiba A. Al-Mohammed,; Huda. M. Mahmood, (Iraqi Journal of Pharmaceutical Sciences, 2024)
Pseudomonas aeruginosa is a common cause of nosocomial infections worldwide, and infections caused by this bacterial organism are difficult to eradicate because it is intrinsically resistant or less susceptible to several antimicrobial agents. The study aimed to identify the genotype distribution or frequency of virulence factors genes (algD, pilA, and pilB) involved in alginate and the type 3 system of carbapenem-resistant of P. aeruginosa local isolates. The genotype distribution of 25 carbapenem-resistant P. aeruginosa involving the alginate was noted with the highest frequency (100%), the genes that encoded for pilin structural subunits were noted with the lowest frequency (4%) for pil B gene, and pil A gene showed (92%). The results of the PCR detection revealed the high spread of the alg D gene, all resistant isolates contained this gene at the same time these isolates were 100% producing biofilm, alginate production is a significant factor of biofilm-associated virulence. chi-square showed a significant association between the biofilm intensity and carbapenem resistance (X² = 14.62, P < 0.023).